Biokonserwatyzm i preferencja status quo - Lewandowski, Wojciech (ETHICS IN PROGRESS, 2015)
Bioconservative view holds that we should prevent dissemination of biomedical inteventions enhancing human capacities. One of arguments against this view shows that it is based on status quo bias which gives unjustified preference for actual state of affairs. According to this argument reasons against human enhancement are not conclusive. The aim of this article is to show the possibility of the interpretation of the bioconservative view, under which it is possible avoiding the status quo bias objection.